Photosynthesis as a discrete biochemical process - M. Štetina; J. KrempaskÝ (Discrete Dynamics in Nature and Society)
It is shown that the existence of a multioscillatory and chaotic regime observed in the photosynthesis could be explained on the basis of logistic equations, i.e., using a discrete approach. Transforming known phenomenological differential equations describing the photosynthesis into the discrete formalism it is possible to demonstrate that by change of control parameters such equations generate the very well known Feigenbaum‘s scenario of the duplication of states including the possibility of the transition into a chaotic regime. The multioscillatory states characterised by even, and what is surprising, also by odd number of “subcycles” are generated at some special combinations of values of control parameters.